A study of the relationship between internet addiction, psychopathology and dysfunctional beliefs. - Taymur, Ibrahim; Budak, Ersin; Demirci, Hakan; Akdağ, Hatice Alkan; Güngör, Buket Belkız; Özdel, Kadir (Computers in Human Behavior, 2016)
Background and aims Psychopathological symptoms, particularly depression and anxiety, increase with the severity of Internet Addiction (IA). In this study, we aimed to assess the relationship of severity of IA and Dysfunctional Attitudes (DA) with psychopathological characteristics. Methods Two hundred and twelve university students were included in the study. The subjects were assessed using the Internet Addiction Scale (IAS), the Symptom Checklist (SCL-90) and the Dysfunctional Attitude Scale (DAS). Results The subjects were divided into three groups according to the IAS, which was conducted to screen for IA: no addiction, mild and moderate/high addiction. 108 (50.9%) of the subjects were found to have no addiction, 70 (33.01%) to have a mild addiction and 34 (16.03%) to have a moderate/high addiction. Psychopathological symptoms and dysfunctional attitudes increase with the severity of IA. In addition to the psychopathologic features, dysfunctional attitudes have limited effects on explaining the IA. Conclusions In the cognitive-behavioral treatment of IA, focusing on a perfectionist attitude and a need for approval, which are part of a dysfunctional attitude, may be beneficial.